Regression analysis in assessing lecturers' health-related quality of life (HRQoL) during Covid-19 pandemic / Nur Niswah Naslina Azid @ Maarof...[et al.] - Azid @ Maarof, Nur Niswah Naslina; Mustafa, Nur Munirah; Halimi, Hani Arissa; I Ramle, Nurul Atikah; Ismail, Idari (Unit Penerbitan UiTM Kelantan, 2021)
The COVID-19 world health crisis has affected the mental and psychological health as well as the well-being of individuals around the world. However, little is known about the impact of the COVID-19 pandemic on the quality of life among lecturers. This research aims to determine the socio-demographic variables such as age, gender, income level, containment zone on health-related quality of life (HRQoL) among lecturers during the COVID-19 pandemic. Besides, this study also aims to establish the relationship between individual variables (anxiety, perceived susceptibility, perceived severity, optimistic bias), social support (family, friends, and significance other) towards HRQoL. A cross-sectional study was used where participants were recruited using simple random sampling. The sample consisted of 52 lecturers in UiTM Kelantan from both campuses of UiTM Machang and UiTM Kota Bharu. Since the purpose of this study is to analyze the individual HRQoL, hence the EQ-5D index calculator was used. The analysis of data was done using SPSS software to analyze the relationships between variables. In conclusion, from the multiple linear regression model, it shows that the perceived susceptibility, working years, and education level significantly affect the health-related quality of life among lecturers.